Evaluating the effectiveness of training programmes in enhancing employability and reducing unemployment in South Africa: a training programmes and employability perspective - Olivier, Johan (University of Pretoria, 2026)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2025.